The Effect of Al-Quran Murottal Therapy on Pain and Anxiety Scores in Preoperative Patients in Inpatient Rooms - Endang Sri Iryani; Ismansyah; Rivan Firdaus (Formosa Journal of Science and Technology, 2023)
Pain and anxiety are manifestations that are often experienced by preoperative patients and one of the pain management and anxiety levels is murottal Al-Quran Surah Ar Rahman therapy (juice 27 to the 55th sura and 78 verses) which is given to inpatients at RSUD dr. Abdul Rivai Berau. This type of research is quantitative research with a queasy experimental research design with randomized, pre-test, and post-test with control design types. Based on the results of the Wilcoxon signed rank test, the p-value <(0.000<0.05) was obtained. So, it can be concluded that there is an effect on pain and anxiety levels in preoperative patients before and after the administration of murottal Al-Quran therapy.